MEDITATION: CONCENTRATION AND INSIGHT - Goleman, Daniel (Journal of Dharma, 1977)
How many people here meditate regularly or have learned to meditate at one time? How many would like to try? We will then in the course of my presentation. My interest in meditation really was a side effect of my training in clinical psychology. At about the same time as I was doing my therapy practices I started to meet people who had been meditating for some time. I also was rather dismayed to notice that the people who were supervising my therapy at the best hospitals-Harvard Medical School and so on-and were highly thought of in their own profession, psycho-analysis parti- cularly, were not as (I do not know quite how to put it) "finished beings" as I wished them to be. They were just human beings like everyone else, although I had been somehow led into the expectation that they would be something more than that. How- ever, people who had been meditating, although they were also human beings, seemed in the course of the meditation experience, especially if they were long-term practitioners, Yogis and so on, to have gone through and somewhat beyond the goals of therapy. I was very- intrigued by this. It seemed to me that meditation might have some usefulness as an adjunct to therapy. For that reason I became very interested in meditation and, finally, went to India to study it. Because my background is in psychology and my interest is in both meditation as an applied psychological technique and in religion, in its root or esoteric forms, my psycho- logical training influences my approach to our discussion of meditation.